An analysis of households' credit markets in Ethiopia and Malawi. - Fichera, Eleonora (2010)
The aim of this thesis is to analyse formal and informal credit in Ethiopia and Malawi. As credit markets in developing economies are dominated by informal institutions, the analysis of the interaction between formal and informal institutions is crucial to understanding how welfare improvements can be achieved. The thesis begins with an explanation of the motives for demanding credit. It then focuses on analysing the existence, diffusion and persistence of informal nance in developing economies. Much research on this topic remains hamstrung by the quality and availability of data and by the lack of empirical models, constraining the meaningful identification of the characteristics of the localities where informal institutions operate. The central idea of the first essay is to develop an empirical model that explains the determinants of participation in informal credit arrangements. We adopt an endogenous switching regression model of access to informal credit where the availability of a particular type of informal arrangement varies across clusters in rural Ethiopia. This strategy allows for taking into account substitutability between sources as well as household and cluster socioeconomic characteristics. The second essay exploits the idea that banks can crowd out informal borrowing in Malawi by creating microfinance institutions that acquire information in innovative ways. We adopt propensity score matching and find that the creation of a specific microfinance programme reduces informal borrowing. The third essay uses the credit limit variable to test liquidity constraints and the spillover hypotheses in Malawi. A ten percent increase in the informal credit line increases households' demand for informal credit by more than nine percent. We also find that a 10 percent increase in the credit limit of a microfinance programme reduces the informal demand by four percent, partly explaining the coexistence of formal and informal credit institutions.